Digital marketing as an object of intellectual property - Vydrya, E. S.; Pererva, P. G. (My University, 2023)
It has been proven that the key factor of digital marketing is to work as closely as possible with the audience, which is currently setting trends in digital marketing. Since this field is quite dynamic, new trends appear as quickly as they lose their relevance, so in order to effectively contact the audience, brands have to constantly adapt to changes in public preferences.
Цифровий маркетинг як об’єкт інтелектуальної власності
Keywords: information technology; marketing; intellectual property; social networks; advertising